Effect of China’s Land Resource Allocation Method on Enterprise Technological Innovation: Promoting or Inhibiting - Ma, Jintao; Hu, Qiuguang; Wei, Xinyi (Frontiers in Environmental Science, 2022)
Whether the land resource allocation method with Chinese characteristics can continue to play a positive role must be explored in the context of high-quality development. This study is based on the panel data of A-share listed non-financial insurance enterprises from 2006 to 2018. The proportion of industrial land area in urban construction land area to characterize land resource allocation methods and analyzes the effect of China's land resource allocation methods on enterprise technological innovation. Results show that (1) the land resource allocation methods of the large-scale transfer of industrial land and the restricted transfer of commercial and residential land inhibit enterprises from technological innovation. (2) The inhibition is heterogeneous given the nature of the enterprise and the degrees of technology intensity and regional differences. The effect is greater on state-owned enterprises and those in high-tech industries and eastern cities. (3) The increase in corporate R&D expenditure and government subsidies weakens the negative effect of China's land resource allocation method to a certain extent. This study maintains that the reform of land resource allocation methods should be promoted following local conditions, the role of the market should be fully utilized, and the subjective initiative of local governments should also be mobilized to promote the overall transformation of the economy and society to innovation-driven development effectively.